Reliability of the Modified O’Sullivan Functional Balance Test in Person with Spinal Cord Injury - Chinsongkram, Butsara; Pluempitiwiriyawej, Suthisa; Hongthong, Somchanok; Boonsinsukh, Rumpa (Journal of Food Health and Bioenvironmental Science, 2023)
The modified O’Sullivan functional balance test is a short and easy scale that is commonly used in clinical practice, but this test lacks of standardized instructions that may affect its reliability. This study aimed to determine the reliability of the modified O’Sullivan functional balance (mOFB) test in persons with spinal cord injury. Various test instructions were given and VDO recorded in twelve chronic spinal cord injuries (lesion level C5-L5). Inter-rater and intra-rater reliability were determined by 5 physical therapists who have clinical experience ranging from 1 to 10 years. All raters scored the patient’s performance from from observing the video twice, 7 days apart. Inter-rater and intra-rater were calculated by interclass correlation coefficient (ICC). The mOFB test showed excellent intrarater reliability (ICCs range from 0.93 (0.86-0.98) to 0.96 (0.92-0.99)), whereas interrater reliability ranged from poor to moderate (ICC range from 0.38 (0.12-0.69) to 0.53 (0.26-0.80). The different test instructions including posture alignment adjustment before testing, amount of resistance, and amount and direction of reaching led to decreased intra-rater reliability to poor and moderate. This study confirmed that a lack of a clear testing instructions and grading criteria decreased the reliability of the modified O’Sullivan functional balance test.